2016
DOI: 10.3847/0004-637x/821/2/117
|View full text |Cite
|
Sign up to set email alerts
|

COLD MILKY WAY H i GAS IN FILAMENTS

Abstract: We investigate data from the Galactic Effelsberg-Bonn Hi Survey (EBHIS), supplemented with data from the third release of the Galactic All Sky Survey (GASS III) observed at Parkes. We explore the all sky distribution of the local Galactic Hi gas with |v LSR | < 25 km s −1 on angular scales of 11 to 16 . Unsharp masking (USM) is applied to extract small scale features. We find cold filaments that are aligned with polarized dust emission and conclude that the cold neutral medium (CNM) is mostly organized in shee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 50 publications
10
95
2
Order By: Relevance
“…1 with isophotes. These structures are typical for the filamentary CNM described by Kalberla et al (2016).…”
Section: Source Selectionmentioning
confidence: 73%
See 1 more Smart Citation
“…1 with isophotes. These structures are typical for the filamentary CNM described by Kalberla et al (2016).…”
Section: Source Selectionmentioning
confidence: 73%
“…For the northern sky there is the Galactic Effelsberg-Bonn Hi Survey (EBHIS, , in the south the Parkes Galactic All Sky Survey (GASS, McClure-Griffiths et al 2009;Kalberla et al 2010). Kalberla et al (2016), merging EBHIS with the 3rd release of the GASS (GASS III, Kalberla & Haud 2015), have shown that the cold neutral medium (CNM) in the local vicinity is mostly organized in filaments. A comparison with structures measured by Planck at 353 GHz (Planck Collaboration et al 2016) disclosed that the CNM filaments are well aligned with the thermal dust emission.…”
Section: Introductionmentioning
confidence: 99%
“…New methods of analysis are required that do not rely on the assumption of Gaussian statistics or weak deviations from it and are sensitive to morphological and topological properties of the random fields. For example, the nature of filamentary structures (Kalberla et al 2016) prominent in both observations and many numerical simulations of interstellar gas requires reliable determination of their dimensions (see Makarenko et al 2015;Kalberla et al 2016, for examples of such analysis). The need for new methods of statistical comparison between theory and observations is discussed in an insightful review of Goodman (2011) and by Koch et al (2017) who employ genus statistics, a topological measure earlier applied to the matter distribution in the cosmic web (Gott et al 1987, and many later papers).…”
Section: Discussionmentioning
confidence: 99%
“…XXXII 2016;Planck Collaboration Int. XXXVIII 2016;Kalberla et al 2016), the GMF orientation is correlated with the structure of matter as traced by H i or dust emission. Our modelling does not include the density structure of the ISM, nor does it include the correlation between matter and the magnetic field orientation; however, the polarization layers could phenomenologically represent distinct matter structures along the LOS.…”
Section: Density Structure Of the Ismmentioning
confidence: 99%
“…An important result is that in the diffuse ISM, the filamentary structure of matter is observed to be statistically aligned with the GMF (McClure-Griffiths et al 2006;Clark et al 2014;Planck Collaboration Int. XXXII 2016;Kalberla et al 2016).…”
Section: Introductionmentioning
confidence: 99%